2008
DOI: 10.1021/cm702933h
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Ruthenium Catalysts for Ring-Opening Metathesis Polymerization-Based Self-Healing Applications

Abstract: Self-healing polymers based on ring-opening metathesis polymerization incorporate first-generation Grubbs’ catalyst as the polymerization initiator during a healing event. However, the use of this catalyst imposes limitations due to the catalyst’s chemical and thermal instability typically encountered in processing and curing of epoxy resins. In this work, we compare three variations of Grubbs’ catalysts (first generation, second generation, and Hoveyda−Grubbs’ second generation) for use in self-healing polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
88
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(97 citation statements)
references
References 30 publications
5
88
0
3
Order By: Relevance
“…One way this problem can be addressed is using the monomers described above with faster healing kinetics (such as ENB and exo-DCPD), which require lower loadings of catalyst to achieve high degrees of cure in a reasonable time period. Additionally, increasing the rate of catalyst dissolution in healing agent, either by treating the catalyst particles to have a larger surface area 81 or selecting catalysts and healing agents with inherently matching chemical compatibilities, 82,83 is known to reduce the amount of catalyst required in a self-healing polymer. Also, Rule et al showed that by encasing Grubbs' catalyst in a protective wax shell, a 10-fold decrease in catalyst loading can achieve similar healing to an unprotected catalyst.…”
Section: Microencapsulated Healing Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…One way this problem can be addressed is using the monomers described above with faster healing kinetics (such as ENB and exo-DCPD), which require lower loadings of catalyst to achieve high degrees of cure in a reasonable time period. Additionally, increasing the rate of catalyst dissolution in healing agent, either by treating the catalyst particles to have a larger surface area 81 or selecting catalysts and healing agents with inherently matching chemical compatibilities, 82,83 is known to reduce the amount of catalyst required in a self-healing polymer. Also, Rule et al showed that by encasing Grubbs' catalyst in a protective wax shell, a 10-fold decrease in catalyst loading can achieve similar healing to an unprotected catalyst.…”
Section: Microencapsulated Healing Agentsmentioning
confidence: 99%
“…[53][54][55][56] Wilson and co-workers developed an approach to calculate the average retention of healing capabilities r avg of polymers and composites that were initially fabricated at different temperatures. 82 This calculation is shown in equation (8) are equal to the average peak load value on loaddisplacement curves of healed specimens whose polymer matrices' were previously post-cured at 35 and 125uC respectively. While this equation has been used infrequently in the literature thus far, it will be useful to guide the processing of self-healing composites that contain thermally sensitive components but require curing cycles at elevated temperatures 192 ) and the presumably low stiffness of Ghosh and Urban's UV healable chitosan/ polyurethane based polymers (the mechanical properties of this system were not explicitly stated, but inferred from their ability to readily undergo unassisted crack closure 193 ) may further limit them to coating applications, where structural integrity is not of the upmost importance.…”
Section: Healing Evaluationmentioning
confidence: 99%
“…Despite their similar approach, distinct methods reported a variety of quality and preparation processes of self-healing polymers since the breakthrough made by White and co-workers [5]. One of the most extensively used healing agent is dicyclopentadiene (DCPD) [5][6][7][8][9][10] contained in urea-formaldehyde (UF) copolymer shells. It works through ring-opening metathesis polymerization (ROMP) and requires solid (Grubbs' first generation) catalyst to be dispersed in the applied epoxy matrix.…”
Section: Introductionmentioning
confidence: 99%
“…The monomer most often used as the healing agent for the manufacture of these first ingenious systems is dicyclopentadiene (DCPD) [5,29]. Very recently, however, blends of DCPD/5-ethylidene-2-norbornene (DCPD/ENB) or DCPD/ 5-norbornene-2carboxylic acid have also been proposed [30]. Thermosetting auto-repair polymers, which have been proposed so far, include Grubbs' first-generation catalyst (G1); [5,17,[29][30] and currently, the possibility of applying other ruthenium catalysts for ringopening metathesis polymerization-based self-healing applications is being evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, however, blends of DCPD/5-ethylidene-2-norbornene (DCPD/ENB) or DCPD/ 5-norbornene-2carboxylic acid have also been proposed [30]. Thermosetting auto-repair polymers, which have been proposed so far, include Grubbs' first-generation catalyst (G1); [5,17,[29][30] and currently, the possibility of applying other ruthenium catalysts for ringopening metathesis polymerization-based self-healing applications is being evaluated. This system is a challenge for epoxy structural composites: however, some drawbacks have to be re-evaluated in order to be fully applied to advanced applications.…”
Section: Introductionmentioning
confidence: 99%